DESIGN OF DRIVEN PILE FOUNDATION AND JETTY INTERNATIONAL FERRY TERMINAL BATAM CENTRE - GITA PRAMESHWARI, GALUH
International Ferry Terminal Batam Centre is an international ferry port located on the northern shore area of Batam Island, Riau Islands Province. International Ferry Terminal Batam Centre has four area main function: two-story area of a terminal building, vehicle parking area, jetty, and dropping system for public transportation. This final project focuses on the design of driven pile foundation system of terminal building and jetty. The driven pile foundation of the terminal building designed with the specification of 600 mm diameter and applied at the depth of 9 meter. The total amount of piles are 276 units and the configuration of pile groups used is one pile cap consist of two piles. The range of group settlement is between 6-9 cm with qualified differential settlement (<1/300). Lateral deformation occurs with a range between 2 -12 mm for three types of loading (static load, nominal earthquake, strong earthquake) calculated using ENSOFT GROUP and LPILE. The range of bending moment is 46-120 kNm with qualified bending moment capacity of the pile which has been determined by the manufacturer. The driven pile foundation of the jetty is designed with the modeling principles of soil strength against lateral force which is modeled as a spring to obtain stiffness values that can be calculated using ENSOFT LPILE and SAP2000. The driven pile foundation of jetty designed with the specification of 800 mm diameter and applied at the depth of 23 meter. The total amount of piles are 18 units. Mooring facilities that used for the ferry are 2x2 meters fenders with 5 meters spacing and bollards with the capacity of 15 tons. The design of reinforcement for plate and beam elements are done in accordance with Indonesian National Standard (SNI).